Supervision and guidance of talent development of P.E. schools with the PDCA model - Xu, J.; Fang, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The expanded enrolment of colleges and universities in China, in combination with world economic globalization, has imposed a great pressure on the employment of the graduates of P.E. colleges and universities. The deteriorating quality of the graduates is contributing to the severe employment situation. This paper proposes to use the PDCA model to supervise and guide talent development in P.E. schools to enhance the overall development of the students and make graduates more employable. Methods Literature review and comparative analysis. Results The main causes of deterioration in the quality of graduates from P.E. schools include: 1. Lack of supervision and management of talent development; 2. The inappropriate arrangement of subjects, lack of professional development and the school`s inefficient response to social needs; 3. The current talent development model for P.E. in schools not satisfying the market demand for quality graduates. Discussion The PDCA model is a scientific process for overall quality management, which is often used in enterprises to supervise and manage product quality. It also works well in talent development of P.E. schools. On the basis of research the conclusions are as follows: 1. The appropriate application of the PDCA model can be used as the scientific basis for optimizing and enhancing talent and the quality of P.E. schools. The four steps of planning, implementation, examination and action should be applied throughout the course of development. 2. The traditional PDCA model can be updated by adding supervision and guidance sections. A specific organization for supervision and guidance could be established with the help of the administrative, teaching, learning and research sections of the school. The current traditional monotonous development model can be transformed into the comprehensive development model. For example, transforming training of specific competence to training of comprehensive competence, and from development of comprehensive competences with one major to the development of comprehensive competences with two majors.